2013
DOI: 10.1097/wnr.0000000000000009
|View full text |Cite
|
Sign up to set email alerts
|

Role of central arginine vasopressin receptors in the analgesic effect of CDP-choline on acute and neuropathic pain

Abstract: Recent studies have demonstrated that arginine vasopressin (AVP) plays a crucial role in pain modulation. In addition, our previous studies have proven that centrally administered cytidine-5'-diphosphate-choline (CDP-choline; citicoline) elicits an analgesic effect in different pain models in rats. Given that CDP-choline enhances central and peripheral vasopressin levels, the present study was designed to investigate the role of central AVP receptors in the analgesic effect of CDP-choline in acute and chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Citicoline has an extensive effect on the cholinergic system and could act as a choline donor to increase the synthesis of acetylcholine. The central cholinergic activating effect of citicoline has been emphasized, with this effect explaining the cardiovascular [103][104][105][106][107][108][109][110], metabolic [111][112][113][114][115][116][117][118], and antinociceptive effects [119][120][121] of the drug, together with effects on signaling systems [122][123][124][125][126][127].…”
Section: Experimental Datamentioning
confidence: 99%
“…Citicoline has an extensive effect on the cholinergic system and could act as a choline donor to increase the synthesis of acetylcholine. The central cholinergic activating effect of citicoline has been emphasized, with this effect explaining the cardiovascular [103][104][105][106][107][108][109][110], metabolic [111][112][113][114][115][116][117][118], and antinociceptive effects [119][120][121] of the drug, together with effects on signaling systems [122][123][124][125][126][127].…”
Section: Experimental Datamentioning
confidence: 99%
“…The human AVPR1A gene is located in the long arm of chromosome 12 (12q14.2) (Babb, Fernandez-Duque, & Schurr, 2010; Bagdas et al, 2013; Birnbaumer, 2000; Thibonnier et al, 1994; Thibonnier et al, 1996; Walum et al, 2008; Yang et al, 2010; Young, Nilsen, Waymire, MacGregor, & Insel, 1999). The protein coded from this gene behaves as a receptor for arginine vasopressin and belongs to a family of G-protein coupled receptors that include oxytocin.…”
Section: Resultsmentioning
confidence: 99%
“…Vasopressin has been described as playing a crucial role in the modulation of pain and several studies have shown that AVP can regulate the pain process in the brain through the mediation of central cholinergic and opioidergic systems (Bagdas et al, 2013; Mogil et al, 2011). In a recent study, a three-way interaction between, genetics (AVPR1A, re10877969), sex, and acute stress in both the in both mice and humans was demonstrated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations